2022
DOI: 10.25182/jgp.2022.17.1.47-56
|View full text |Cite
|
Sign up to set email alerts
|

An Additional Adequate Water Intake Increases the Amniotic Fluid Index in Pregnant Women with Oligohydramnios: A Systematic Review

Abstract: This systematic review aimed to answer whether an additional amount of water intake can increase the Amniotic Fluid Index (AFI) in pregnant women with oligohydramnios. Article searches were conducted and data was obtained from "SCOPUS", "EBSCO", "PUBMED", "COCHRANE" and "Google Search" databases using the following keywords: "hypovolemic", "dehydration" "pregnancy" "outcome", "hydration". "water intake", "oligohydramnios", and "amniotic fluid index". We used MeSH headings (hydration pregnancy) for search keywo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…5,27,28 Previous studies have demonstrated that inadequate water intake can affect amniotic fl uid index (AFI), and suffi cient water intake may increase AFI. 29 A higher proportion of dehydrated urine samples was associated with a lower birth weight when tested in the second trimester. 16 The fi ndings from this study are signifi cant because of the increased demand for water during pregnancy and the widespread failure of pregnant women in many parts of the world to consume enough amounts of water.…”
Section: Mulyani Et Al 2021mentioning
confidence: 96%
“…5,27,28 Previous studies have demonstrated that inadequate water intake can affect amniotic fl uid index (AFI), and suffi cient water intake may increase AFI. 29 A higher proportion of dehydrated urine samples was associated with a lower birth weight when tested in the second trimester. 16 The fi ndings from this study are signifi cant because of the increased demand for water during pregnancy and the widespread failure of pregnant women in many parts of the world to consume enough amounts of water.…”
Section: Mulyani Et Al 2021mentioning
confidence: 96%